2018
DOI: 10.1159/000486361
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Therapy for Selected Patients with PIM1 Kinase-Positive Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma: A Pilot Study

Abstract: We reported that PIM1 kinase is expressed in the lymphocytes of patients with chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL). Quercetin, a naturally occurring flavonoid, is a dietary supplement and inhibits many kinases, including PIM1, in vitro. Under an Institutional Review Board-approved protocol, we performed an open-label, single-arm pilot study to evaluate the antitumor activity of quercetin in patients with CLL/SLL. Q-ForceTM chews were administered orally, 500 mg twice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Merkel et al reported that PIM1 kinase had the potential as a target for cancer therapy [37]. Besides, many reports have shown that the activity of PIM1 could be inhibited by quercetin [38,39]. In our study, Figure 5 showed that the quercetin regulated the PIM1, which was involved in the breast cancer.…”
Section: Discussionsupporting
confidence: 58%
“…Merkel et al reported that PIM1 kinase had the potential as a target for cancer therapy [37]. Besides, many reports have shown that the activity of PIM1 could be inhibited by quercetin [38,39]. In our study, Figure 5 showed that the quercetin regulated the PIM1, which was involved in the breast cancer.…”
Section: Discussionsupporting
confidence: 58%
“…34,35 Besides, quercetin owned the phytoestrogen-like activity, which is likely via the interaction with the estrogen receptor β. 36,37…”
Section: Resultsmentioning
confidence: 99%
“…34,35 Besides, quercetin owned the phytoestrogen-like activity, which is likely via the interaction with the estrogen receptor β. 36,37 We mapped the 143 predicted targets into the KEGG pathway database. Many targets are related to the metabolic pathways (43 targets), cancer pathways (23 targets), PI3K-Akt signaling pathway (21 targets), Ras signaling pathway (20 targets), and so on.…”
Section: Acs Omegamentioning
confidence: 99%
“…Among these, its antileukemic effect has attracted increasing attention in recent years. In a pilot study, QUE demonstrated the potential of stabilizing the rising lymphocyte counts of patients with PIM1 kinase-positive chronic lymphocytic leukemia 2. The antileukemic action of QUE was also verified in a xenograft model of human leukemia HL60 cells 3.…”
Section: Introductionmentioning
confidence: 92%